Building software for simulation : theory and algorithms, with applications in C++ - Nutaro, James (Hoboken, N. J. : John Wiley & Sons, 2010)
'This book offers a concise introduction to the art of building simulation software. It clearly demonstrates the five skills necessary for building simulations of complicated systems: abstractions for simulation dynamic systems; basic simulation algorithms for continuous and discrete event simulations; combining continuous and discrete event simulations into a coherent whole; strategies for testing a simulation; and theoretical foundations of the modeling constructs and simulation algorithms. This is indispensable reading for software programmers, developers, and engineers, and students in related courses'--
'This book will be used as an introduction to the design and implementation of simulation software, as a reference for fundamental abstractions that are useful when building object-oriented simulation programs, and as a collection of specific algorithms for simulating dynamic systems'--
Includes bibliographical references and index.
Keywords: Computer simulation; C++ (Computer program language